Clinical and Biochemical Characteristics of Dengue Infections in Children From Sri Lanka - Umesh Jayarajah MBBS; Manohari Madarasinghe MD; Damayanthi Hapugoda MD; Upul Dissanayake MD; Lakshika Perera MBBS; Vibhavee Kannangara MBBS; Champika Udayangani MBBS; Ranga Peiris MBBS; Pamodh Yasawardene MBBS; Ishan De Zoysa FRCS; Suranjith L. Seneviratne MD, PhD (SAGE Publishing, 2020)
Introduction: Analyzing dengue disease patterns from different parts of the world should help us formulate more evidence based treatment guidelines and appropriately allocate limited healthcare resources. Therefore, we described the disease characteristics of hospitalised pediatric patients with dengue infections from Sri Lanka during the 2017 dengue epidemic. Methods: Clinical and biochemical characteristics of pediatric dengue patients treated at a secondary care hospital in Sri Lanka from 1 June 2017 to 31 August 2017 were analyzed. Our findings were compared with previous pediatric dengue studies in Asia. Results: A total of 305 patients (number of males = 184(60%); mean age = 8.6 years) were analyzed. DF (Dengue Fever)-245 (80.3%), DHF (Dengue Hemorrhagic fever)-I:52 (17%), DHF-II:7 (2.3%), and DHF-III:1 (0.3%). Significant associations were found between DHF and abdominal symptoms/signs and overt bleeding manifestations ( P  < .001). Time of onset of the critical phase was variable (Day 3: 12%, Day 4-5: 78%, Day 6: 5%, and Day 7: 5%). Platelet and white-cell counts (WBC) were significantly lower in DHF than DF; liver enzyme derangement was mild and was similar in the DHF and DF subgroups. None had cardiac, renal, or neurological manifestations and all recovered uneventfully. Conclusion: In Sri Lankan pediatric dengue patients, we found abdominal symptoms and signs, decreased WBC and platelet counts and bleeding manifestations were to be significantly associated with DHF. Liver enzyme derangement did not predict DHF. The time of onset of the critical phase was difficult to predict due to the considerable variations noted.